BAHASA INGGRIS SEBAGAI LINGUA FRANCA DALAM DUNIA TRANSPORTASI - Abimanto, Dhanan; Aprillina, Aprillina; Oktavia, Ariana (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
In an increasingly globalized world, English language plays a crucial role in communication in the transportation field, involving various countries and cultures. This article aims to investigate the role of English as a lingua franca in the transportation industry and emphasize its importance in facilitating communication among professionals in the sector. Through literature analysis and relevant sources, this article explains that English enables professionals such as pilots, flight attendants, port officers, and air traffic controllers to communicate smoothly and effectively. Proficiency in English also expedites information exchange and ensures safety and operational efficiency, especially in emergency situations or when working with multinational teams. Furthermore, the standardization of English in international air navigation rules, maritime traffic systems, and land transportation regulations ensures consistent communication and mutual understanding among professionals worldwide. This helps to avoid misunderstandings that could have adverse effects on safety and security. Moreover, English language proficiency facilitates mobility and global connectivity in the transportation industry. Professionals who master English have broader access to international career opportunities and can interact with customers, business partners, and colleagues from various countries. This strengthens business relationships, enhances customer satisfaction, and facilitates the exchange of knowledge and innovation. Therefore, a good understanding and utilization of English as the primary language are crucial in maintaining the smooth functioning and effectiveness of the increasingly complex transportation industry.